1972
DOI: 10.3133/ofr721978
|View full text |Cite
|
Sign up to set email alerts
|

Tectonics of the Indonesian Region

Abstract: The plate-tectonic evolution of a region can be deduced by following the assumptions that subduction zones are characterized by ophiolite, melange, wildflysch, and blueschist, that intermediate and silicic calc-alkaline igneous rocks form above Benioff zones, and that truncations of orogenic belts indicate rifting. Interrelatioships provide crosschecks, as do marine geophysical data. Southeast Asia and "Sundaland" are an aggregate of small continental fragments. Late Paleozoic subduction westward beneath Malay… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
584
2
11

Year Published

1984
1984
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 283 publications
(603 citation statements)
references
References 5 publications
6
584
2
11
Order By: Relevance
“…Tanabala, Tanamasa, Pini, Tuangku, and Bangkaru lie off the west coast of Sumatra, an area of great tectonic activity (Hamilton 1979), so they were not used in this study. Finally, I suspect that three islands used by Wilcox (Bali, Penang, and Singapore) were heavily disturbed before sampling took place, and so I do not include them.…”
Section: Methodsmentioning
confidence: 99%
“…Tanabala, Tanamasa, Pini, Tuangku, and Bangkaru lie off the west coast of Sumatra, an area of great tectonic activity (Hamilton 1979), so they were not used in this study. Finally, I suspect that three islands used by Wilcox (Bali, Penang, and Singapore) were heavily disturbed before sampling took place, and so I do not include them.…”
Section: Methodsmentioning
confidence: 99%
“…1) drains part of the Central Borneo Massif, which is dominated by CretaceousEocene age sediments. These rocks are accretionary complexes and forearc basin deposits that formed during the Tertiary opening and spreading of the South China Sea (Hamilton, 1979;Hutchison, 1989Hutchison, , 1996. They are composed of folded and faulted, finegrained siliciclastics, with minor amounts of carbonates.…”
Section: Physiographic Setting Climate and Previous Workmentioning
confidence: 99%
“…Further to the west, the tectonic setting becomes more complicated with interactions between Halmahera, the Molucca Sea Plate and Sulawesi while east of 148°E subduction of the Solomon Sea Plate occurs beneath the South Bismarck Plate on the New Britain Trench [Hamilton, 1979].…”
Section: Introductionmentioning
confidence: 99%
“…[4] Previous studies have suggested that convergence may occur on the NGT [e.g., Hamilton, 1979;Cooper and Taylor, 1987;Puntodewo et al, 1994;Tregoning et al, 2000] along with partitioning of normal convergence and left-lateral slip in the FTB [e.g., Abers and McCaffrey, 1988;Puntodewo et al, 1994] (Figure 1). The lowlands of New Guinea south of the FTB are part of the rigid Australian Plate [Hamilton, 1979;Kreemer et al, 2000].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation